THE REFLECTIONS OF INTERFAMILY RELIGIOUS BELIEFS CONFLICTS ON ROMANTIC RELATIONSHIPS: A SOCIOLOGICAL AND PSYCHOLOGICAL STUDY (Isagoge - Journal of Humanities and Social Sciences, 2025)
This article examines the reflections of religious belief differences between families on romantic relations from a sociological and psychological perspective. The literature shows that religious belief plays a central role in the value system of individuals, and that belief -based expectations among families are often decisive in the choice of partner. Especially in families with different religious or sectarian backgrounds, the romantic relations of couples are shaped by social norms, cultural values ​​and family pressures. The study is based on systematic examination of the relevant literature as a method. Research in the field of psychology may cause religious incompatibilities in individuals may cause anxiety, identity complexity and attachment problems; The sociology literature reveals that these differences affect not only individuals but also the family institution and social structure. The findings point to the points in which the literature is common: Religious belief differences lead to damage to conflict, communication problems and a sense of belonging in romantic relationships. However, some research also shows that if couples develop flexible religious attitudes, relationships can be more harmonious. As a result, religious belief differences affect not only individual psychological experiences but also social adaptation processes in modern societies. For this reason, it is important to evaluate the sociological and psychological dimensions of religious belief differences together in understanding the dynamics of domestic and romantic relationships.
Keywords: Religious Faith; Family Conflict; Romantic Relations; Sociology; Psychology